Li/Mn-Rich Cathode Materials with Low-Cobalt Content and Core-Shell Particle Design for High-Energy Lithium Ion Batteries. Issue 6 (9th April 2020) - Helbig, Jonathan; Beuse, Thomas; Siozios, Vassilios; Placke, Tobias; Winter, Martin; Schmuch, Richard
Abstract : Li/Mn-rich positive electrode materials are widely known for their high energy content, which exceeds that of current cathodes significantly. Their implementation in practical high-energy lithium ion batteries has to date been hindered by various technical challenges, most of all, their insufficient long-term charge/discharge cycling performance. Here, a new concept for designing core–shell (CS) materials for this class is introduced, which is based on cathode particles, which are specifically designed to have an anionic redox-rich core and a shell with reduced anionic redox. This material design approach aims to overcome the drawback of having the sensitive anionic redox at the electrolyte/active material interface, and, therefore, extenuating the phase degradation from layered- to spinel- or even rock salt-structure. In this work, the effect of a CS particle design with a Co-free, Mn-rich core and a Co-containing shell with lower Mn content is studied. The spherical cathode particles, produced by a Couette Taylor Flow Reactor, enable a superior electrochemical performance with excellent initial Coulombic efficiencies of 90%–95% and improved long-term cycling performances compared to the reference materials, consisting of the pure core or pure shell composition.